#### Answer

(a) $-3-2i$
(b) $2+8i$

#### Work Step by Step

(a) $(3-6i)-(6-4i)=3-6-6i+4i=-3-2i$
(b) $4i(2- \frac{1}{2}i)=8i-2i^{2}=8i-2*-1=8i+2=2+8i$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) $-3-2i$
(b) $2+8i$

(a) $(3-6i)-(6-4i)=3-6-6i+4i=-3-2i$
(b) $4i(2- \frac{1}{2}i)=8i-2i^{2}=8i-2*-1=8i+2=2+8i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.